Conclave [videorecording (Blu-Ray)] - Straughan, Peter; Fiennes, Ralph; Tucci, Stanley; Lithgow, John, 1945-; Msamati, Lucian, 1976-; Castellitto, Sergio, 1953-; Rossellini, Isabella; O'Byrne, Brian F.; Diehz, Carlos; Niniże, Merab, 1965-; Loibl, Thomas, 1969-; Bertelmann, Volker, 1966-; et al. (Focus Features, 2024)
Conclave follows one of the world's most secretive and ancient events--selecting the new Pope. Cardinal Lawrence is tasked with running this covert process after the unexpected death of the beloved Pope. Once the Catholic Church's most powerful leaders have gathered from around the world and are locked together in the Vatican halls, Lawrence uncovers a trail of deep secrets left in the dead Pope's wake, secrets which could shake the foundations of the Church.